Renewable Energy Embedded Sustainable Supply Chains with Methane Harness: The Gateway to ASEAN Strategy Illustration with Mixed Model Analysis - Sen, Salil K.; Mokkhamakkul, Tartat (International Journal of Energy Economics and Policy, 2022)
Intent, initiative, immersion, impact manifest through the renewable energy embedded sustainable supply chains. The value-add is more enhanced with COP26 determination to curb methane minimum minus thirty percent. The change obviously embeds benefits, through intent on societal empowerment, initiative on water waste energy rehaul, immersion with gender aligned supply chains. This paper is on the construct of mixed method based qualitative methodology on value-add change that embeds benefits in the renewable energy embedded sustainable supply chains with methane harness. Embedded energy in supply chains can now focus on innovation retaed to methane and not alone carbon dioxide. Developing regions are vibrant with economic activity that proliferate supply chains. They innately depend on water waste energy footprint. There is resonating need for positioning sustainable supply chains with renewable energy that is gender aligned. Methane is a ultra-potent greenhouse gas that has a win win focus on adoption of renewable energy as well as attain sustainability of energy needs of supply chains. Methane traps one hundred times more heat when present in the atmosphere. Focus on methane is potent as it gets removed within a decade, in contrast to carbon dioxide that lingers over centuries. The linkgage options through innovation, intent, impact is a contribution of this paper. Supply chain resource corridors are tenable to potential renewable inclusion. The possibility of varying the impacts of different values of the independent variables, future research can confirm the extent of renewable energy adoption with sustainable supply chain growth. One could also design for variance on the changes of location or habitats, that can define the need of a distributed and differentiated range of combinations. A metric could be designed which is responsive to varying combinations of water quality, waste parsimony and renewable energy minus methane feasibility.